Effectiveness of a group intervention to enhance resilience and improve the well-being of family caregivers of dementia patients - Loma-Ramos, Sara; Fernández-Martínez, Elena; González-García, Alberto; Bello-Corral, Laura; Sánchez-Valdeón, Leticia (Frontiers in Psychiatry, 2025)
IntroductionResilience is a key psychological resource for managing the emotional and physical demands associated with caring for people with dementia. It promotes psychological stability and protects caregiver health. However, evidence on structured interventions specifically designed to strengthen resilience in this population remains scarce. This study aimed to evaluate the effectiveness of a group-based intervention to enhance resilience in dementia caregivers, primary outcome, and to determine whether effects persisted three months post-intervention. Caregiver burden, coping strategies, and social support were examined as secondary outcomes.MethodsA quasi-experimental study with a single-group pre-test/post-test design was conducted with data collected at three time points: baseline (T1), post-intervention (T2), and three months post-intervention (T3). Sociodemographic characteristics were recorded, and resilience was measured using the CD-RISC 10. Caregiving burden was assessed with the Zarit Burden Interview, coping strategies with the CSQ Questionnaire, and perceived social support with the MOS Social Support Survey. The Wilcoxon signed-rank test was used for multiple comparisons (T1–T2–T3).ResultsA significant increase in resilience was observed at post-intervention (T1–T2; p = 0.036), maintained at three-month follow-up (T1–T3; p = 0.040). Significant differences were found in caregiver burden (Zarit) between T2–T3 (p = 0.033), and in coping strategies: problem-solving (T2–T3, p = 0.032; T1–T3, p = 0.021), open emotional expression (T1–T2, p = 0.011; T1–T3, p = 0.041), and use of religion (T1–T2, p = 0.026). No significant changes were found in perceived social support.ConclusionsThe intervention effectively enhanced resilience, improved adaptive coping strategies, and reduced caregiver burden. Healthcare professionals are encouraged to promote such interventions to support the well-being of dementia caregivers.